Testing Output-inflation Trade-off: A Note - Venus, Khim-Sen Liew; Lim, Kian-Ping; Puah, Chin Hong (Researchgate, 2006)
This study estimates the Asai (1999) proposed simplified BMR model (Ball et al., 1988) and ARY model (Akerlof et al., 1988) using quarterly data from Malaysia, Thailand, Japan and US. Unlike other earlier authors, we ensure that our models’ residuals are free from serial correlation and ARCH effects. For the ARY model, Malaysia and US show strong evidence for new Keynesian model, while Thailand and Japan produce inconclusive results. As for the BMR model, all countries provide strong evidence for new Keynesian model. Our finding implies that government generally plays a significant role in altering the economy’s business cycle. Besides, this study suggests that future researchers should do and report residuals diagnostic tests to show the viability of their results.